The Effectiveness of the Problem-Based Learning Model on the Critical Thinking Skills of Grade XI Students at MAN 1 Central Lombok - Nisa Hiidayatullah; Ziadatul Fatimah (Yayasan Siti Widhatul Faeha Salahudin Syawal, 2025)
Critical thinking skills are fundamental cognitive abilities that play a crucial role across many facets of life by enabling people to analyze, assess, and solve problems. The purpose of this study is to examine how students’ critical thinking skills are affected by problem-based learning paradigms. A quasi-experimental design with a non-equivalent control group—also referred to as a pretest-posttest untreated control group design—is used in this quantitative investigation. Purposive sampling was used to get the research sample. This study used a 10-item essay test to assess students’ critical thinking skills. According to the study’s findings, the significance level value was 0.033, which was less than α of 0.050. It suggests that problem-based learning paradigms impact students’ critical thinking skills. These findings suggest that, to accommodate different cognitive styles, learning procedures should be flexible and varied.